The dilemma of innovation management - Lukman, Najah; Abdul Wahid, Khalid; Ismail, Fathiyah; Harun, Nur Syikri (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
Trott (2017) asserts that there will always be a fundamental conflict in any organization between the demands of creativity and stability. It would be extremely difficult for businesses to set aside time in the busy schedule of regular operations to search for new information, learn what is going on in the rivals' camp, or even learn about global events.